2019
DOI: 10.1002/pon.5072
|View full text |Cite
|
Sign up to set email alerts
|

Loneliness as a mediator of the relationship of social cognitive variables with depressive symptoms and quality of life in lung cancer patients beginning treatment

Abstract: Objective Loneliness, or the discrepancy between perceived and desired level of social connectedness, is an understudied but important psychosocial factor in cancer patients. The current study investigated the relationship between loneliness, depressive symptoms, quality of life, and social cognitive variables (eg, stigma, social constraint, and cancer‐related negative social expectations), and explored loneliness as a mediator of the relationship between social cognitive variables and depressive symptoms and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 42 publications
2
21
0
Order By: Relevance
“…However, these emotions may be particularly challenging for patients with a history of anxiety or depression, or who are already experiencing heightened distress related to cancer. Greater loneliness has been associated with worse quality of life and greater depressive symptomology in lung cancer patients, highlighting the potential negative consequences of COVID‐19‐related isolation for patient wellbeing 9 . Clinicians should regularly screen for symptoms of distress and loneliness using brief, validated measures 10 and continue to refer patients to psychosocial services when appropriate.…”
Section: Discussionmentioning
confidence: 99%
“…However, these emotions may be particularly challenging for patients with a history of anxiety or depression, or who are already experiencing heightened distress related to cancer. Greater loneliness has been associated with worse quality of life and greater depressive symptomology in lung cancer patients, highlighting the potential negative consequences of COVID‐19‐related isolation for patient wellbeing 9 . Clinicians should regularly screen for symptoms of distress and loneliness using brief, validated measures 10 and continue to refer patients to psychosocial services when appropriate.…”
Section: Discussionmentioning
confidence: 99%
“…A paper published recently by oncologists presents the psychological challenges cancer patients have faced during the pandemic, including loneliness, fear, conflicts regarding treatment, feeling helpless, frustration, anger, sadness and depression (Garutti et al, 2020 ). Loneliness has been associated with a decrease in quality of life and depressive symptoms in lung cancer patients (Hyland et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…western countries (5)(6)(7)(8)(9)(10). However, this is the first study conducted in East Asia, especially in the field of lung cancer.…”
Section: Discussionmentioning
confidence: 95%
“…A systematic review indicated that social isolation and loneliness were associated with higher mortality rates, regardless of whether they were linked to underlying medical conditions (5). Hyland et al also reported that loneliness might be a manifestation of depressive symptoms and low quality of life (6). Social isolation also has mental and physical effects.…”
Section: Introductionmentioning
confidence: 99%